2019
DOI: 10.1111/cpr.12675
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative potential of human dental pulp stem cells in the treatment of stress urinary incontinence: In vitro and in vivo study

Abstract: Objectives To evaluate the regenerative potential of human dental pulp stem cells (hDPSCs) in an animal model of stress urinary incontinence (SUI). SUI, an involuntary leakage of urine, is due to physical stress involving an increase in bladder pressure and a damage of external urethral sphincter affecting muscles and nerves. Conventional therapies can only relieve the symptoms. Human DPSCs are characterized by peculiar stemness and immunomodulatory properties and might provide an alternative tool for SUI ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…After being cultured in specific condition for several weeks, DPSCs elongate and display a myoblast-like phenotype. These DPSCs express specific myocytic immunohistochemical markers such as MyoD1, myosin, and MHC [ 79 , 80 ]. Other than the myogenic potential, DPSCs also preserve the capability to differentiate into adipocytes [ 81 , 82 ] and pancreatic cell lineage [ 83 , 84 ].…”
Section: Dpscsmentioning
confidence: 99%
See 1 more Smart Citation
“…After being cultured in specific condition for several weeks, DPSCs elongate and display a myoblast-like phenotype. These DPSCs express specific myocytic immunohistochemical markers such as MyoD1, myosin, and MHC [ 79 , 80 ]. Other than the myogenic potential, DPSCs also preserve the capability to differentiate into adipocytes [ 81 , 82 ] and pancreatic cell lineage [ 83 , 84 ].…”
Section: Dpscsmentioning
confidence: 99%
“…Moreover, DPSCs in prevascularized, scaffold-free, microtissue spheroids can successfully regenerate vascular dental pulp-like tissue, which provides a new strategy for endodontic treatment and makes dentin-pulp regeneration possible [ 85 ]. The clinical application potential of DPSCs is not only in dentistry but also in treatments for other diseases, such as craniofacial bone defects [ 86 ], muscle regeneration [ 87 ], myocardial infarction [ 88 ], Alzheimer's disease [ 89 ], nervous system injuries [ 90 ], Parkinson's disease, diabetes [ 91 ], stress urinary incontinence [ 80 ], osteoarthritis [ 92 ], and liver diseases [ 93 ].…”
Section: Dpscsmentioning
confidence: 99%
“…Following migration, neural crest cells generate the majority of craniofacial tissues, including tooth, fat, muscle, bone and cartilage tissues, as well as cranial peripheral ganglia and nerves, among other cell types, such as melanocytes (Pisciotta et al, 2020). It has been widely demonstrated that hDPSCs are able to differentiate toward lineages belonging to all the three germ layers, as a matter of fact these stem cells can commit to glial cells and participate in peripheral nerve regeneration (Carnevale et al, 2018), contribute in restoring urethral sphincter contractile function (Zordani et al, 2019), reduce fibrosis and ameliorate muscle trophism in Duchenne Muscular Dystrophy mouse model (Pisciotta et al, 2015b), besides promoting bone tissue regeneration in critical size calvarial defects (Pisciotta et al, 2012). Further evidence of the regenerative potential of hDPSCs is documented by their capability to promote vascularization in regenerating tissues in vivo and supported by their expression of VEGF (Laino et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Either exfoliating deciduous teeth or intentionally harvested adult teeth can provide dental pulp stem cells (DPSCs) for regenerative purposes (Gronthos et al, 2000). DPSCs direct regeneration by in vivo multipotential differentiation, including liver, dental pulp, bone, muscle and nerve, besides promoting vascularization of the regenerating tissues (Gandia et al, 2008;Ikeda et al, 2008;Yamada et al, 2011;Bianchi et al, 2017;Zordani et al, 2019). DPSCs of neural crest derivation may provide particularly valuable function in nerve regeneration as demonstrated by their phentoype (Carnevale et al, 2018), their differentiation along neurogenic lineages and functional studies demonstrating DPSC-mediated functional regeneration of siatic nerve (Ullah et al, 2017).…”
Section: Exosome Isolation From Dental Tissuementioning
confidence: 99%